Serological Evaluation of Hepatitis B Virus in Out Patient Department Patients of a Private Hospital in North-West India - Smita Sood (Medsci Publications, 2013)
Background: Globally, Hepatitis B is one of the most common infectious diseases. India has a strong private health care system which can be utilized for capturing a useful and large amount of clinical information. Objective: To determine the seroprevalence of Hepatitis B surface antigen (HBsAg) in patients attending outpatient departments (OPDs) of a private hospital in Northwest India over a period of 2 years. Methodology : A retrospective study (January 2010 - December 2011) was conducted on 9515 patients presenting to various OPDs of a 210 bedded private hospital in Jaipur , Rajasthan who submitted their serum sample to the lab for serological evaluation of Hepatitis B. HBsAg was screened by electrochemiluminescence and positive samples were cross checked by a rapid immuno-chromatography test. Results: HBsAg seroprevalence was observed in 1.73% of the OPD population. It was observed to be 1.85% in males and 1. 52% in females. Highest HBsAg seroprevalence was noted in age group 51-60 years. Seroprevalence of HBsAg in Surgical OPDs was 0.84% and in Medical OPDs was 2.54 %. Conclusion: The results of this study may not be a reflection of the situation in the Jaipur city population, but can be of assistance for the mapping of viral hepatitis prevalence and may be helpful in planning public health interventional strategies.